Perencanaan Produksi Tenun Ikat Ina Sabu di Kota Kupang: - Koro, Enjelina Devitriana; Enjelina Devitriana Koro; Yoseba Pulinggomang; Erna G. Giri (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This research is a case study with the object of research on Tenun Ikat Ina Sabu located at Jalan Sukun I, RT 009 / RW 004, Oepura Village, Maulafa District, Kupang City, East Nusa Tenggara. The purpose of this study was to determine and explain the production planning of Tenun Ikat Ina Sabu in Kupang City. The types of data used are qualitative and quantitative. Data collection techniques in this study were interviews, observations, questionnaires and documentation. While the data analysis techniques used are Linear Trend and Break Even Point (BEP). The results of the Linear Trend calculation show that in 2024 Tenun Ikat Ina Sabu will produce 383 pieces of sarong, 358 pieces of blanket and 284 pieces of shawl, then the amount produced for 2025, 414 pieces of sarong, 332 pieces of blanket and 303 pieces of shawl, and the amount produced for 2026, 445 pieces of sarong, 402 pieces of blanket and 322 pieces of shawl. The results of the Break Even Point (BEP) analysis in 2023 show that if Tenun Ikat Ina Sabu produces 1,060 pieces of ikat weaving or around Rp.90,343,129, then the company does not make a profit or loss.